Co-ordination between xylem anatomy, plant architecture and leaf functional traits in response to abiotic and biotic drivers in a nurse cushion plant. (27th February 2021) - García-Cervigón, Ana I; García-López, María A; Pistón, Nuria; Pugnaire, Francisco I; Olano, José Miguel
Abstract: Background and Aims: Plants in dry Mediterranean mountains experience a double climatic stress: at low elevations, high temperatures coincide with water shortage during summer, while at high elevations temperature decreases and water availability increases. Cushion plants often act as nurses by improving the microclimate underneath their canopies, hosting beneficiary species that may reciprocally modify their benefactors' microenvironment. We assess how the nurse cushion plant Arenaria tetraquetra subsp. amabilis adjusts its hydraulic system to face these complex abiotic and biotic constraints. Methods: We evaluated intra-specific variation and co-ordination of stem xylem anatomy, leaf functional traits and plant architecture in response to elevation, aspect and the presence of beneficiary species in four A. tetraquetra subsp. amabilis populations in the Sierra Nevada mountains, southern Spain. Key Results: Xylem anatomical and plant architectural traits were the most responsive to environmental conditions, showing the highest mutual co-ordination. Cushions were more compact and had smaller, more isolated conductive vessels in the southern than in the northern aspect, which allow minimization of the negative impacts of more intense drought. Only vessel size, leaf mass per area and terminal branch length varied with elevation. Nurse cushions co-ordinated plant architecture and xylem traits, having higher canopy compactness, fewer leaves per branch and fewer, more isolated vessels than non-nurse cushions, which reflects the negative effects of beneficiary plants on nurse water status. In non-nurse cushions, plant architecture co-ordinated with leaf traits instead. The interacting effects of aspect and elevation on xylem traits showed that stress due to frost at high elevation constrained xylem anatomy in the north, whereas stress due to drought had a parallel effect in the south. Conclusions: Trait co-ordination was weaker under more demanding environmental conditions, which agrees with the hypothesis that trait independence allows plants to better optimize different functions, probably entailing higher adjustment potential against future environmental changes.